IT PROJECT MANAGEMENT: USING FLEXIBLE METHODOLOGIES - SKRYPNYK, TETIANA; VOZNYUK, LEONID; MANDZIUK, YELYZAVETA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The rapid development of information technology and dynamic consumer needs changes force companies to optimize both external business conditions and internal organizational processes. One of the key issues in ensuring competitiveness in the IT services market is effective business management, which can adapt to rapid changes in the IT sector, customer requirements, oversaturation of the market with products and at the same time allows to work quickly, efficiently and cost-effectively. Accelerated development of the IT sector requires modern and advanced methodologies and tools for project management. Flexible methodologies, such as Agile management and the Lean, Scrum and Kanban methodsbased on it, help organize work efficiently to produce a quality software product and adapt more quickly to new requirements. It is essential to consider flexible project management methodologies in the IT field, particularly Agile - management and derived methods Lean, Scrum, Kanban. An overview of key aspects of Agile - management will summarize this management methodology’s main advantages and disadvantages and form a complete understanding of the current approach to effective management of the company and a particular project. The article is devoted to identifying promising, agile project management methodologies in the IT sphere and ways of their successful application. It reviews basic aspects of Agile management and reveals the most popular tools of agile methodologies, such as Scrum and Kanban. The principles of Agile are highlighted, and the value of agile methodologies for developing teamwork and optimizing tasks in a team is shown. The advantages and disadvantages of Scrum as one of the most popular Agile tools are highlighted. The review of actual scientific works is carried out, defining questions, connected with organization and conducting of management processes in IT sphere, which are provided due to Agile methodologies. Attention is paid to the defining principles and algorithms that are used in IT projects, to organize work on the production of a software product. The difference between Kanban and Scrum methodologies is defined, the contents of the mentioned tools, key aspects and principles of their application and use are defined. The importance of the software product Jira is emphasized, which plays an important role in the distribution of functional tasks in the team and fixing the identified errors. The need for further study of the application of Agile methodologies, principles and practices in the project management of IT companies was noted.